Odpowiedzi

2010-02-04T19:34:10+01:00
A) 3x-5-2x+2-5x-4 dla x = -3
-4x-7=-4*(-3)-7=12-7=5

b) 2x²- 4x+7+x²-5x-8 dla x= -1
3x²-9x-1=3*(-1)²-9*(-1)-1=3+9-1=11

c)4a-3b-2-6a+b-3 dla a= -2 dla b= -1
-2a-2b-5=-2*(-2)-2*(-1)-5=4+2-5=1
39 2 39
2010-02-04T19:34:59+01:00
A) 3x-5-2x+2-5x-4=-4x-7=12-7=5
b)3x²-9x-1=3*(-1)²-9*(-1)-1=3+9-1=11
c)-2a-2b-5=-2*(-2)-2*(-1)-5=4+2-5=1
36 1 36
Najlepsza Odpowiedź!
2010-02-04T19:37:16+01:00
A]
3x-5-2x+2-5x-4=-4x-7
x=-3
-4×-3-7=5
b]
2x²-4x+7+x²-5x-8=3x²-9x-1
x=-1
3×(-1)²×-9×(-1)-1=11
c]
4a-3b-2-6a+b-3=-2a-2b-5
a=-2
b=-1
-2×-2-2×-1-5=1
11 3 11